Comparative employment relations in the global economy - Frege, Carola M., 1965-; Kelly, John E., 1952- (Routledge, Taylor & Francis Group, 2020)
"Employment Relations is widely taught in business schools around the world. However, an increasing emphasis is being placed on the comparative and international dimensions of the relationships between employers and workers. It is becoming crucial to consider today's work and employment issues alongside the dynamics between global financial and product markets, global production chains, national and international employment actors and institutions, and the ways in which these relationships play out in different national contexts. Comparative Employment Relations in the Global Economy meets this need by presenting a cross-section of country studies, including the UK, Germany, the USA, Brazil, India, Russia, China and South Africa, alongside integrative thematic chapters covering essential topics such as theoretical approaches, collective representation and employment regulation. This second edition benefits from: Careful updates to theory and real-life developments A new chapter on employment relations in Italy Fuller treatment of topics such as labour migration, gender and discrimination, global value chains and corporate governance A more logical ordering of chapters, with globalization issues appearing earlier This textbook is the perfect resource for students on advanced undergraduate and postgraduate comparative and international programmes across areas such as employment relations, industrial relations, human resource management, political economy, labour politics, industrial and economic sociology, regulation and social policy"--